Walter Mitty’s Personality Transformation in The Secret Life of Walter Mitty (2013): Plato’s Allegory Cave - Maheswari Callula; Sumayah (Faculty of Language and Literature, University of Surakarta, 2025)
A movie directed by Ben Stiller, The Secret Life of Walter Mitty (2013), offers a visually stunning narrative that has captivated audiences worldwide. This study examines the transformation of Walter Mitty’s personality from the perspective of Plato’s Allegory of the Cave. The research aims to explore how Walter’s journey symbolizes the transition from illusion to self-discovery. Employing a qualitative method, this analysis focuses on narrative and visual elements that reflect the allegorical process of emerging from the